Organoleptic Evaluation Of Kue Semprong Substitution Of Mocaf Flour (Modified Cassava Flour) - Khairani, Muthia; Endrairanti, Hadaina Nur; Najah, Jazilah Zatayumni; Salsabila, Sahda Maura; Normalitasari, Safira Desi; Ayu Palupi, Ghentari Endang (Universitas Negeri Padang, 2023)
Kue semprong is one of the traditional Indonesian cakes made by baking using a special mold that is later rolled. The main ingredient of kue semprong is rice flour but in this research, it is substituted with mocaf flour. This is because rice consumption is increasing day by day, so to overcome this, it can be replaced with mocap flour. In addition, the nutritional content between rice flour and mocap flour is not much different. The ingredients used in making mocaf flour kue semprong are mocaf flour, tapioca flour, granulated sugar, vanilla, SP developer, eggs, liquid margarine, coconut milk, and salt. The method used in this research is the experimental description method to determine the organoleptic test on the kue semprong. The results obtained from the organoleptic test are that the kue semprong has a creamy yellow color with a little brownish, sweet taste, savory aroma, and crunchy texture.